(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The objective of the study is to design a drilling fluid that prevents differential pressure pipe sticking tendency caused by drilling fluid with fly ash that is an industrial waste generated from the combustion of coal. To this end, drilling fluid samples were prepared with different particle sizes obtained through the sieving and grinding process and increasing concentrations of fly ash. Differential pipe sticking tests of the samples were performed by applying 3.447 MPa (500 psi) pressure and using a Fann Model 21150 Differential Sticking Tester in order to determine how the coefficient of sticking and torque reading varied with the fly ash. From the results, it was observed that the coefficient of sticking and torque reading of the water-based drilling fluids decreased up to a specific concentration as the concentration of fly ash increased. Furthermore, particle size analysis illustrated that the coefficient of sticking and torque of the drilling fluid differs depending on the particle size of fly ash introduced. The drilling fluid designed with ground fly ash demonstrated lower sticking coefficient and torque reading than that of drilling fluids formulated with raw and sieved fly ashes. The experimental study revealed that fly ash is a promising additive in the mitigation of differential sticking tendency caused by water-based drilling fluids.